Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Lu, Yao; Yu, Peng; Zhang, Yan; Chen, Jian; Liu, Tao; Wang, Han; Liu, Hongjun (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E50ref and the effective internal friction angle φ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E50ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.